الأسباب المؤثرة على حكم السفر بعد نداء الجمعة الثاني دراسة فقهية تحليلية: The Factors Influencing the Ruling on Traveling After the Second Call to Friday Prayer: An Analytical Jurisprudential Study - Alobeidli, Abdulla Mohamed Ghaith; Jibo, Salihu Musa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تتمثل مشكلة البحث في دراسة حكم إنشاء السفر بعد النداء الثاني لصلاة الجمعة، وبيان الأسباب المؤثرة على هذا الحكم، وإظهار خلاف الفقهاء في ذلك. ويهدف إلى بيان حكم إنشاء السفر يوم الجمعة بعد أذانها الثاني، وبيان الحالات التي استثناها الفقهاء من هذا الحكم، وقياس المستجدات الحديثة عليها، وقد سلكت فيها المنهج التحليلي، والمنهج الاستنباطيّ؛ فهو تحليلي عند معرفة سبب الخلاف في المسألة وباعث كل فريق على اختياره الفقهي، واستنباطي عند دراسة النصوص والاستدلال بها وإلحاق النوازل الحادثة بنظيراتها في كلام الفقهاء -رحمهم الله-، وقد توصلت إلى جملة من النتائج أبرزها: أنّ الراجح من قولي العلماء تحريم السفر يوم الجمعة بعد الزوال إلا إذا ترتب على المكلف ضرر بفوات رفقته، أو علم أنّه سيدرك الجمعة في طريقه، أو تعيّن عليه السفر فورًا لنحو إنقاذ نفس أو مالٍ، أو إدراك وقوف بعرفة، وأنّه لا يجوز تقصد جعل رحلات السفر بعد الزوال بحيث تفوت عليه الجمعة بعد لزومها عليه بدخول وقتها إلا ألا يجد وقتًا غير ذلك أو يترتب عليه ضررٌ بتغيير الوقت. ABSTRACT This study investigates the legal ruling on initiating travel after the second call to the Friday prayer, with the aim of identifying the factors that influence this ruling and highlighting the juristic disagreements surrounding it. The research further seeks to clarify the ruling on initiating travel on Friday following its second call, to outline the exceptional cases identified by the jurists, and to apply analogy (qiyās) to contemporary developments. The methodology adopted combines both analytical and deductive approaches: analytical in identifying the reasons behind the juristic disagreement and the motives that led each school of thought to its position, and deductive in examining the relevant texts, adducing evidence, and extending juristic principles to contemporary issues in light of classical discussions. The study reached several key findings, most notably: the preponderant opinion among scholars is that initiating travel after midday on Friday is prohibited, unless the individual would suffer harm by missing his travel companions, or is certain that he will still be able to catch the Friday prayer on his way, or is required to travel immediately for urgent reasons such as saving a life or property, or catching the standing at ʿArafah. Furthermore, it is impermissible to deliberately schedule journeys after midday in a way that would cause one to miss the Friday prayer once its time has entered, unless no alternative time is available or changing the time would result in harm.